PENERAPAN PROGRAM ADIWIYATA DI SMP NEGERI 13 PALEMBANG - Sitisyarah, Kania; Mustika, Ramadhanita (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
This research was qualitative, which describes the application of Adiwiyata program at State Secondary School 13 Palembang. The instruments used in this research were interview, observation and previous finding and theories related to the characteristics of Adiwiyata school. Based on the analysis, the application of Adiwiyata program at State Secondary School 13 Palembang were environmentally sound policy, the implementation of environment based curriculum, participative environment based activities, management of friendly environment which support facilities. As Adiwiyata School, State Secondary School 13 Palembang has achieved a series of achievements, such in May 2013, this State Secondary School won the I Adiwiyata (school environmental level) city level. In June of the same year, State Secondary School 13 Palembang being the winner of Adiwiyata (provincial-level of environmental school). Then, in December 2013, State Secondary School 13 Palembang returned to achievement by winning I Adiwiyata (environmentally sound schools) at the national level. In 2015, this State Secondary School won the I Adiwiyata (environmentally independent school) with 17 schools. After successfully becoming an independent Adiwiyata school, State Secondary School 13 Palembang is currently heading to ECOASEAN Adiwiyata School by creating environmental innovation from plastic waste.Â Keywords: Adiwiyata, ECOASEAN, State Secondary School 13 Palembang